‘RepresentaXión’ de un muxe: la identidad performática de Lukas Avendaño - Prieto Stambaugh, Antonio (Latin American Theatre Review, 2015)
Lukas Avendaño is an emerging Mexican performance artist whose recent work constitutes a queer performatic intervention of Mexican nationalistic representations, particularly that of Zapotec Tehuana women. Avendaño embodies the complex identity of muxes, or male homosexuals from the Tehuantepec Isthmus where he was born. His cross-dressing performance interweaves ritual dances with autobiographical passages and actions that involve audience members to challenge the widely-held view of a gay-friendly indigenous culture and point towards the existence of lives that negotiate pain and loneliness with self-affirming pride. The article concludes with a theoretical argument regarding the way Avendaño’s work queers the very concept of representation to suggest the possibility of representaXión, a sensual, disidentificatory, and body-based performance.